Kajian Kriminologis Bentuk Kekerasan Guru Terhadap Siswa - Nasrul, Nasrul; Wardaningsih, Wardaningsih; Hayati, Nur (Jurnal Litigasi Amsir, 2023)
This research aims at what factors cause criminal acts of teacher violence against students in Parepare City, and to determine efforts to overcome the occurrence of criminal acts of teacher violence against students in Parepare City. This research uses normative-empirical research. The results of the research show that the factors causing violence perpetrated by teachers against their students at school are various, namely lack of supervision of student behavior from parents, violations accompanied by physical punishment, and the environment. And it is also tied to violence from a human rights perspective.